Effect of Dietary Exogenous Enzyme Supplementation on Enteric Mucosal Morphological Development and Adherent Mucin Thickness in Turkeys - Ayoola, Ayuub A.; Malheiros, Ramon D.; Grimes, Jesse L.; Ferket, Peter R. (Frontiers in Veterinary Science, 2015)
Anti-nutritional factors (ANFs) in feed ingredients can challenge gut health and reduce nutrient utilization. Birds typically activate their innate immune system as a protective response against the adverse effects of ANF, which often involves the secretion of mucin. Although dietary supplementation of exogenous enzymes are commonly used to alleviate the adverse effects of ANF on apparent nutrient digestibility, little is known about how they affect gut health, particularly in relation to the morphological development and mucin secretion of enteric mucosa. We carried out two trials to examine the effect of dietary supplementation of different types of exogenous enzymes on gut health of by accessing the effect of jejunum morphological development and ileal enteric adherent mucin thickness layer in turkeys. Dietary β-mannanase supplementation reduced ileal adherent mucin thickness layer (804 vs 823 μg/g; p < 0.05), while a commercial blend of xylanase, amylase, and protease (XAP) reduced ileal adherent mucin layer thickness (589 vs 740 μg/g; p < 0.05); thus reducing the apparent endogenous loss of nutrients. Both enzyme supplements also affected gut morphological characteristics. In comparison to the control treatment, dietary β-mannanase supplementation improved the jejunum tip width (219 vs 161; p < 0.05), base width (367 vs 300; p < 0.05), surface area (509,870 vs 380, 157; p < 0.05) and villi height/crypt depth ratio (7.49 vs 5.70; p < 0.05), and XAP improved the crypt depth (p < 0.05). In conclusion, dietary supplementation of exogenous enzymes may help alleviate the adverse effects of ANF on nutrient utilization by directly or indirectly removing the mucosal irritation that stimulates enteric mucin secretion.